Beyond Tenure: A Quasi-Experimental Causal Analysis of Community Forest Management on Peatland Biodiversity, Carbon Stocks, and Management Efficacy in Sumatra - Jasmila Tanjung; Sarah Armalia; Jovanka Andina; Caelin Damayanti (Indonesian Community Empowerment Journal, 2025)
Indonesia's Hutan Desa (HD, Village Forest) program is a cornerstone of global social forestry, yet its causal ecological impacts remain contested. Rigorous, counterfactual-based evidence is urgently needed to validate this policy intervention, particularly in globally critical peat-swamp landscapes. This study employed a quasi-experimental design, using Propensity Score Matching (PSM) to construct a statistically balanced sample of 40 HD (treatment) and 40 non-HD (control) village units in Sumatran peatlands. We analyzed data from 400 1-hectare permanent sample plots (5 plots nested per village). We assessed floral diversity (Shannon-Wiener Index, H'), faunal presence, and ecosystem carbon stocks (Above-Ground, AGB; Soil Organic Carbon, SOC). Causal impacts were quantified using Linear Mixed-Effects Models (LMMs) to account for the nested data structure. We further analyzed the "treatment effect" by modeling dose-response relationships for permit duration and management intensity. After matching, LMMs revealed that HD management has a significant positive causal effect on all ecological outcomes. Floral diversity was significantly higher in HD plots (H' = 2.92) versus control plots (H' = 2.18; F(1, 78) = 48.21, p < 0.001). Total ecosystem carbon stocks (AGB + SOC in top 100cm) were 36% higher in HD units (255.1 Mg C ha⁻¹) compared to controls (187.3 Mg C ha⁻¹; F(1, 78) = 53.09, p < 0.001). This was driven by a significant preservation of SOC. Dose-response models further showed that ecological benefits (such as AGB) accumulate significantly with increased permit duration and that higher management intensity is a strong predictor of biodiversity. In conclusion, our findings provide robust, hierarchical evidence that HD management is an effective conservation and climate mitigation strategy. By establishing tenure, enabling active stewardship, and, crucially, protecting peatland hydrology, the HD model delivers verifiable, causal improvements to biodiversity and carbon stocks.